Universal access in human-computer interaction. users and context diversity : 10th International Conference, UAHCI 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, Proceedings /: users and context diversity : 10th International Conference, UAHCI 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, Proceedings. Part III : (2016) - Unknown
No abstract available